THE INFLUENCE OF SMS BASED ON LOCATION TOWARD PURCHASE INTENTION - Intariani, Diah Dewi; Belgiawan, Prawira Fajarindra (Journal of Business and Management, 2018)
Abstract. There is 308,2 million mobile subscribers in Indonesia (2015) that made the delivery ofmessages by mobile phone with purpose to promote their brand through mobile phone is become the interesting one. Mobile Advertising allows the delivery of information is done by personally and to many people in the same time that make more efficient and hit the right target. Beside that, communication through mobile phone is easy and can be adapted easily by consumer. This study discusses the influence of SMS based on Location towards Purchase Intention. The features of SMS location-based advertising (entertainment, credibility, intrusiveness, informativeness, permission, and customization) have on consumer attitudes and will affect their purchase intentions to the product. This study is a conclusive research with the descriptive design. A quantitative approach is applied by spreading online questionnaire to the closest friends and collecting 300 respondents. The result of this research will be asses using confirmatory factor analysis and structural equation modelling, The findings revealed that all the variable, Customization, entertainment, credibility, informativeness, intrusiveness and permission features have significant effects on creating an attitude towards SMS location-based advertising. In addition, when consumers show a positive attitude towards SMS location-based advertising, it also significantly influences their intention to purchase.Key Words: Attitude, Location-Based Advertising, Purchase Intention, SMSÂ